KEMUNGKINAN DAN BATAS-BATAS KENDALI POLITIS TERHADAP ILMU PENGETAHUAN - Donatus Sermada Kelen (Litbang STFT Widya Sasana Malang, 2003)
The article focuses on the possibilities and the limitations of how far the political control is operating in the field of the science. The dynamics of the scientific development goes into two directions, namely to build up the autonomous position of the science and to make the science being bridled by the social problems from outside. The author tries to show up the possibilities the political control of the science can be done properly in the phase of its historical development, but at the same time the author points out the limitations the political control of the science should face. The article ends up with a description of an ethical problem found in the present times due to the one-sided development of the science, namely being determined and directed by the other interests outside from the science itself.